Here Be Monsters: Imperialism, Knowledge and the Limits of Empire - Macfarlane, Karen E. (Text Matters: A Journal of Literature, Theory and Culture, 2016)
It has become a truism in discussions of Imperialist literature to state that the British empire was, in a very significant way, a textual exercise. Empire was simultaneously created and perpetuated through a proliferation of texts (governmental, legal, educational, scientific, fictional) driven significantly by a desire for what Thomas Richards describes as “one great system of knowledge.” The project of assembling this system assumed that all of the “alien” knowledges that it drew upon could be easily assimilated into existing, “universal” (that is, European) epistemological categories. This belief in “one great system” assumed that knowledges from far-flung outposts of empire could, through careful categorization and control, be made to reinforce, rather than threaten, the authority of imperial epistemic rule. But this movement into “new” epistemic as well as physical spaces opened up the disruptive possibility for and encounter with Foucault’s “insurrection of subjugated knowledges.” In the Imperial Gothic stories discussed here, the space between “knowing all there is to know” and the inherent unknowability of the “Other” is played out through representations of failures of classification and anxieties about the limits of knowledge. These anxieties are articulated through what is arguably one of the most heavily regulated signifiers of scientific progress at the turn of the century: the body. In an age that was preoccupied with bodies as spectacles that signified everything from criminal behaviour, psychological disorder, moral standing and racial categorization, the mutable, unclassifiable body functions as a signifier that mediates between imperial fantasies of control and definition and fin-de-siècle anxieties of dissolution and degeneration. In Imperial Gothic fiction these fears appear as a series of complex explorations of the ways in which the gap between the known and the unknown can be charted on and through a monstrous body that moves outside of stable classification.